Web-based Online Application for Information System of Student Report Card at SLBN Cinta Asih Soreang - Ferry Satria; Hertog Nugroho; Mina Naidah Gani; Usman Hanafi; Rifa Hanifatunnisa; Hanny Madiawati; Maya Rahayu; Nila Novita Sari; Taufik Irfan (Institut Teknologi Nasional, Bandung, 2022)
Monitoring learning outcomes in the form of report cards of competencies from students is a routine agenda of teachers to students in each semester. SLBN Cinta Asih Soreang in collaboration with the Politeknik Negeri Bandung Community Service prgram since 2021 has developed a student report card desktop application.This application has been run and successfully implemented, but not all devices are compatible to run the application. In addition, filling out reports can only be done at school because the desktop application storage can only be stored in a local area. In order to overcome these problems, it is necessary to develop an online-based system for digitizing student achievement reports. The proposed solution is the development of a Web-based online application for an information system for student progress report cards at SLBN Cinta Asih Soreang. The result reveals that more than 90% of participants feel this application is useful and can be utilized in the future.